Analysis of the Distribution of Diabetes Mellitus in Bekasi City, West Java: Risk Factors and Its Prevalence Patterns from 2019-2022 - Nurlin; Nila Hildayani; Nur Isnainin Nur Isnainin; Muhammad Halik Kaslah (Journal of Health Science and Pharmacy, 2026)
Background: Type 2 diabetes mellitus (DM) is a significant global health concern, particularly in developing countries such as Indonesia. In West Java province, the prevalence of DM increased from 1.3% to 1.7% (Republic of Indonesia Ministry of Health, 2018). In 2019, Bekasi City’s health profile reported that 42,517 individuals were living with diabetes. The rising incidence of DM in the population is closely associated with factors such as age, gender, education level, occupation, physical activity, and family history of the disease. Objective: This study aims to determine the prevalence rate of diabetes mellitus in Bekasi City, West Java, from 2019 to 2022 using secondary data derived from the city's health profile. Method: A quantitative descriptive approach was employed in this study, which involved analyzing secondary data obtained from Bekasi City's health profile documents. The data analyzed included the number of diabetes mellitus cases recorded annually. The data were organized into tables and graphs, followed by narrative analysis to identify patterns and trends. Results: The findings of the study revealed fluctuations in the number of diabetes mellitus cases between 2019 and 2022. The number of cases increased from 2019 to 2021, with a notable decline observed in 2022. Genetic factors and dietary patterns were identified as primary contributors to the onset of the disease. Conclusion: The distribution of diabetes mellitus in Bekasi City highlights the importance of individual awareness in adopting healthy lifestyle habits and behaviors. Prolanis, a healthcare service initiative, aims to address this issue by using an intensive approach that combines active participation from diabetes mellitus patients. Keywords: Diabetes Mellitus, disease distribution, prevalence, risk factors of Bekasi City, West Java